Mongolia’s Nuclear-Weapon-Free Status: Unique Approach to Neutrality - Sanallkhundev, Bayasgalan (Mongolian Journal of International Affairs, 2024)
Throughout the modern history of Mongolia, which dates from 1911s, Mongolia sought to defend its independence and sovereignty. After declaring its independence in 1921, Mongolia did not want to be involved in any conflict and tried to be as neutral as possible. However, due to unfavorable international conditions and rivalry among big powers, Mongolia had fallen under the Soviet protectorate from 1921 to 1990s. Having felt immense pressure from both neighbors, neutrality is not new for Mongolia. Due to its unique geographic location, Mongolia has been within the interests of two neighbors which did not allow it to be neutral. Only since the 1990s, Mongolia conducted its own foreign policy. The neutrality was in focus again. Mongolia made many efforts towards neutrality, which adds broader meaning to neutrality. In order to be secure Mongolia has been trying many options towards security assurance through domestic laws, bilateral international agreements and UN resolutions. Mongolia’s nuclear neutrality is closely related to its unique location. There is no other country than Mongolia, which is sandwiched between two nuclear weapon powers, the permanent members of the UN Security Council. This article suggests that Mongolia’s nuclear-weapon-free status can be recognized as one of the options of neutrality in case of nuclear threat or nuclear war.